Clostridium perfringens type‐D enterotoxaemia in cattle: the diagnostic significance of intestinal epsilon toxin. (17th October 2015) - Jones, A. L.; Dagleish, M. P.; Caldow, G. L.
Abstract : The aims of this study were to describe 42 cases of Clostridium perfringens type‐D enterotoxaemia in cattle seen between 2003 and 2014 and to determine the diagnostic value of detecting epsilon toxin in bovine intestinal content. All cases in the series had histological brain changes considered pathognomonic for C. perfringens type‐D enterotoxaemia in sheep and goats and the epsilon toxin of C. perfringens was concurrently detected in the intestinal contents of 15 (36 per cent) cases. The data from the case series indicate that intestinal epsilon toxin has a sensitivity of 56 per cent compared with histology of the brain for diagnosis of bovine C. perfringens type‐D enterotoxaemia. The diagnostic specificity of detecting epsilon toxin in bovine intestinal content was investigated by screening intestinal contents of 60 bovine carcases submitted for postmortem examination. Epsilon toxin was detected in 11 (18 per cent) carcases but no pathognomonic histological brain change was found in any. The specificity of intestinal epsilon toxin was estimated to be 80.4 per cent. These studies demonstrate that for a definitive diagnosis of C. perfringens type‐D enterotoxaemia in cattle histological examination of the brain is essential as the presence of epsilon toxin in the intestinal contents alone is neither sensitive nor specific enough.